Analisis Kandungan Logam berat Cu, Pb dan Zn pada Air, Sedimen dan Bivalvia di perairan Pantai Utara Pulau Bengkalis - Bambang Irawan; Bintal Amin; Thamrin Thamrin (Universitas Riau, 2015)
Analysis of heavy metals Cu, Pb and Zn in water, sediment and bivalves in the Northerncoast of Bengkalis Island Riau Province was conducted in September 2013. Samples were takenfrom 4 stations and environmental parameters such as temperature, pH, salility and current speedwere also measured. The results showed that all the water quality parameters measured in thepresent study were still in the range of tolerable level for aquatic organisms.The mean heavymetals Cu, Pb and Zn concentrations were 0.827; 0.406; 02.104 mg / L in seawater and 42.165;1.892; 78,556 μg/ g in sediment. Meanwhile the concentrations of those metals in bivalve were70.598; 3.762; 186.702 μg/g in Polymesoda expansa and 74.378; 3.903; 129.619 μg/g in Pharellaacutidens. Positive correlations between concentrations of Cu, Pb and Zn in water and sedimentwith concentrations in both bivalves species were found. Based on the PTWI calculation it issuggested that both species of bivalves were still safe to be consumed. Concentrations of heavymetals in sediment in the northern coast of Bengkalis Island were still below the ERL and ERMstandard indicating no serious pressure yet on the living organisms in the surrounding areas.